Pendidikan Kesehatan Teknik Menyusui Terhadap Peningkatan Kemampuan Menyusui Pada Ibu Primipara - Yuni Astuti; Tuti Anggarawati (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2020)
The puerperium is a period that begins a few hours after the birth of the placenta and ends when the uterus organs will return to their pre-pregnancy state which lasts for 6 weeks or about 42 days after delivery. Postpartum often experience problems with breastfeeding. To achieve successful breastfeeding requires knowledge of proper breastfeeding techniques. Mothers can do breastfeeding properly if they are equipped with knowledge and have a positive attitude from health workers. The aim of knowing the effect of health education on correct breastfeeding techniques in post partum primipara. The research design to be carried out using pre-experimental (One group pre-posttest design) and sample selection using purposive sampling. The results showed that there was an effect of health education on breastfeeding techniques on increasing knowledge of postpartum primipara with p value 0.001.primipara, health education, breasfeeding